Imaging of Common Injuries in Gymnastics - Fernández-Gil, María Angeles; Bello Báez, Adán; Bueno Horcajadas, Angel; Calatayud, Julia; Alcalá-Galiano, Andrea; Kassarjian, Ara (Seminars in Musculoskeletal Radiology, 2025)
Gymnastics dates back to ancient Greece and remains one of the most popular sports in the modern Olympics. Due to the extreme forces and ranges of motion required during the various disciplines, injuries are frequent. Additionally, many athletes train and compete during skeletal immaturity that predisposes them to specific injuries. This article briefly reviews some of the more common injuries encountered in the upper limb, axial skeleton, and lower limb in gymnasts with an emphasis on the role of magnetic resonance imaging.
Keywords: gymnastics; Olympic sport; injuries; athletes; magnetic resonance imaging